Stress, anxiety and alkaline or acidic diets in university students during the COVID-19 pandemic - Soto-Alcántara, Lucia Angélica (2022)
Proper nutrition is the human body's first line of defense against various pathogens. against various pathogens. The intake of certain types of food can influence the can influence the risk of various diseases. In times of COVID-19, it is important to analyze the  relationship between the type of diet (alkaline or acidic) and the between the type of diet (alkaline or acidic) and health. The literature reviewed reports on various forms of the relationship between this attribute of diet and general wellbeing.